2013
DOI: 10.1128/jb.02057-12
|View full text |Cite
|
Sign up to set email alerts
|

The Escherichia coli Lpt Transenvelope Protein Complex for Lipopolysaccharide Export Is Assembled via Conserved Structurally Homologous Domains

Abstract: Lipopolysaccharide is a major glycolipid component in the outer leaflet of the outer membrane (OM), a peculiar permeability barrier of Gram-negative bacteria that prevents many toxic compounds from entering the cell. Lipopolysaccharide transport (Lpt) across the periplasmic space and its assembly at the Escherichia coli cell surface are carried out by a transenvelope complex of seven essential Lpt proteins spanning the inner membrane (LptBCFG), the periplasm (LptA), and the OM (LptDE), which appears to operate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
137
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(143 citation statements)
references
References 41 publications
5
137
1
Order By: Relevance
“…LptC does not seem to be a functional component of the IM ABC transporter, as its association with the LptB 2 FG complex does not affect its ATPase activity (8); on the other hand, it appears relevant for proper IM complex assembly (22). Mutational analyses suggest that the interaction of LptC with the IM LptB 2 FG complex is mediated by the N-terminal region of the ␤ jellyroll, whereas its transmembrane domain appears to be dispensable, as a periplasmic soluble version of LptC and a LptC chimera carrying a heterologous transmembrane segment is functional and proficient in Lpt complex assembly (22).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…LptC does not seem to be a functional component of the IM ABC transporter, as its association with the LptB 2 FG complex does not affect its ATPase activity (8); on the other hand, it appears relevant for proper IM complex assembly (22). Mutational analyses suggest that the interaction of LptC with the IM LptB 2 FG complex is mediated by the N-terminal region of the ␤ jellyroll, whereas its transmembrane domain appears to be dispensable, as a periplasmic soluble version of LptC and a LptC chimera carrying a heterologous transmembrane segment is functional and proficient in Lpt complex assembly (22).…”
mentioning
confidence: 99%
“…Such a ␤-jellyroll fold (the Lpt fold) appears to be a key element in driving the assembly of the Lpt machinery. In fact, through these structurally homologous domains, the C terminus of LptC interacts with the N terminus of LptA, and the C terminus of LptA interacts with the N-terminal periplasmic domain of LptD, thus forming a protein bridge that connects the IM and the OM (12,16,20,22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since LptA, LptC, and N-LptD all belong to the OstA structural superfamily [6,21,22], and that LptA physically interacts with the N-terminal of LptD [13], the N-LptD protein might be the docking site for LptA at the OM. LptC was predicted to have a single transmembrane helix (Trp 7 -Asp 29 ) and a large soluble domain [11,18], and its C-terminal part is involved in the interactions with LptA [13] and the N-terminal region is responsible for binding to LptBFG [8]. An earlier study suggested that Due to the structural similarity between LptC and the periplasmic loop of LptF, it is possible that LptF is the candidate part for interactions in this complex [17].…”
Section: Lpta Interacts With Both Im and Om Lpt Complexmentioning
confidence: 99%
“…The ATP hydrolysis within LptBFG is thought to provide energy for LPS transport and facilitate the release of mature LPS from the IM and enable its transfer to the periplasmic carrier molecule LptA [5][6][7]. The LptC anchors to the IM through an N-terminal transmembrane helix to form a complex with LptBFG and its periplasm domain was found to be the essential function region [8]. However, its function is not well understood within the complex LptBFGC [5,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%